2010
DOI: 10.1074/jbc.c110.128280
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tubulin Deglutamylase among Caenorhabditis elegans and Mammalian Cytosolic Carboxypeptidases (CCPs)

Abstract: Tubulin polyglutamylation is a reversible post-translational modification, serving important roles in microtubule (MT)-related processes. Polyglutamylases of the tubulin tyrosine ligaselike (TTLL) family add glutamate moieties to specific tubulin glutamate residues, whereas as yet unknown deglutamylases shorten polyglutamate chains. First we investigated regulatory machinery of tubulin glutamylation in MT-based sensory cilia of the roundworm Caenorhabditis elegans. We found that ciliary MTs were polyglutamylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
125
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(132 citation statements)
references
References 24 publications
7
125
0
Order By: Relevance
“…However, they show a common protein fold similar to peptidases in which two zinc atoms are essential for their activity (such as MH metallopeptidases), implying that metallopeptidase activity might be acquired in independent evolutionary events (37). Because the identified deglutamylases (46) and deglycylases (this study) do not seem to belong to a single well conserved protein family, as in the case of the TTLLs, but share metallopeptidase properties, it is plausible that other metallopeptidases of different clans might exert similar functions in other organisms. Indeed, members of the metallopeptidase clans M14 and M28 and subfamilies M20A and M20D, but none of the M20C, have been identified in the partially annotated genomes of the ciliates T. thermophila and P. tetraurelia as well as in humans and D. melanogaster (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, they show a common protein fold similar to peptidases in which two zinc atoms are essential for their activity (such as MH metallopeptidases), implying that metallopeptidase activity might be acquired in independent evolutionary events (37). Because the identified deglutamylases (46) and deglycylases (this study) do not seem to belong to a single well conserved protein family, as in the case of the TTLLs, but share metallopeptidase properties, it is plausible that other metallopeptidases of different clans might exert similar functions in other organisms. Indeed, members of the metallopeptidase clans M14 and M28 and subfamilies M20A and M20D, but none of the M20C, have been identified in the partially annotated genomes of the ciliates T. thermophila and P. tetraurelia as well as in humans and D. melanogaster (23).…”
Section: Discussionmentioning
confidence: 99%
“…Tubulin glutamylation is performed by some members of the family of TTL-like proteins (25)(26)(27). CCP4 -6 were recently shown capable of removing polyE side chains from tubulin (28,29).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that the carboxyl-terminal (C-terminal) domain of tubulin has strong influence on the interaction with these motor proteins. The interactions between tubulins and motor proteins are regulated by post-translational modifications of the C-terminal tails [64]. In spite of the importance, detailed structure of tubulin C-termini and its relation to their functions have not been clarified even with X-ray or NMR studies [63].…”
Section: Tubulin Protofilamentsmentioning
confidence: 99%